METHODS OF SEMANTIC RESEARCH: COMPONENTIAL CONTEXTUAL, AND OTHER ANALYSES (Modern education and development, 2025)
This paper explores the primary methods of semantic research used to analyze meaning in language. It focuses on componential analysis, which identifies the fundamental semantic features of words; contextual analysis, which derives meaning from linguistic and situational context; and other modern approaches such as cognitive semantics, formal semantics, and distributional semantics. Each method is examined in terms of its theoretical background, practical applications, and limitations. The study highlights how these diverse approaches contribute to a deeper and more nuanced understanding of how meaning operates in human language.